Disease burden for patients with primary immunodeficiency diseases identified at reference hospitals in Guanajuato, Mexico - Guaní-Guerra, Eduardo; Jiménez-Romero, Ana Isabel; García-Ramírez, Ulises Noel; Velázquez-Ávalos, José Manuel; Martínez-Guzmán, Edgar; Sandoval-Ramírez, Eunice; Camacho-Meza, Ignacio (PLOS ONE, 2017)
Background In addition to the deleterious effect on health, there is considerable economic and psychosocial morbidity associated with primary immunodeficiency diseases (PID). Also, the cost of a late diagnosis frequently results in a heavy disease burden on the patient. The objective of this study was to collect and analyze data on patients with PID in the state of Guanajuato in Mexico, to indirectly estimate the burden of the disease. Methods An observational, longitudinal, and comparative study was conducted. A total of 44 patients were included and grouped according to the updated classification of PID. Results The median time elapsed from the onset of symptoms to the reference and diagnosis by a tertiary hospital was of 2.17 (IQR = 6.44) years. Before diagnosis, the number of hospitalizations/year per patient was 0.86 (IQR = 2.28), the number of visit to emergency room/year per patient was 0.92 (IQR = 1.77), the number of doctor’s visits/year per patient was 15 (IQR = 11.25), whereas the school/work absence days per patient were reported in 52.72 (IQR = 56.35) days per year. After diagnosis, 20 patients (45.45%) received IVIG replacement therapy, and all of them presented a significant improvement (p <0.05) in all the mentioned variables. Characteristically, even when patients with PID received IVIG, there was still an important disease burden when comparing them against healthy controls. Complications secondary to PID were detected in 19 patients (43.18%). The reported overall mortality rate was 6.82% (n = 3). Conclusions We were able to indirectly estimate an important disease burden in patients with PID; which is considered to be preventable, at least in part, with effective interventions like health planning, research, collaboration with primary care providers, and generation of policies and practices, in order to improve the quality of life and care of families with PID.